(untitled) (Bangladesh Pharmaceutical Journal, 2022)
Diarrhea is one of the most common reasons for why thousands of people die every year particularly in the underdeveloped and developing country. Furthermore, the identification of new antidiarrheal medication sources has become one of the most prominent areas of contemporary study. In addition, the plants of the Leea species are used traditionally for the treatment of diarrhea in different cultures. Considering this background, present study was to look into the antidiarrheal effects of an ethanolic extract of Leea aequata L. leaves in mice. The castor oil induced diarrhea and the small intestinal transit models were utilized in this study to examine the extract’s potential antidiarrheal efficacy. The extract was given to the test groups in various quantities (100, 200 mg/kg), whereas positive controls got loperamide (3 mg/kg) and negative controls received distilled water (10 ml/kg). In a model of diarrhea caused by castor oil, 200 mg/kg of the extract significantly (p<0.01) decreased the total number of bowel movements. The extracts also demonstrate a substantial (p<0.05) reduction in the frequency of wet defecation at all doses. The onset of diarrhea was extended with dose of the extracts which is statistically significant (p<0.001). At higher doses, the extract caused a significant (p<0.05) reduction in the weight and volume of wet feces. Furthermore, in the charcoal meal test, increasing doses of the extract caused a substantial (p<0.01) reduction in gastrointestinal motility. Phytochemical screening of the extract revealed the presence of flavonoids, alkaloids, tannins, and phytosterols that may play a key role in its antidiarrheal activity. The results of our study indicate that bioactive compounds are present in ethanolic leaf extract of our plant including significant antidiarrheal activity and thus provide the scientific basis for the traditional uses of this plant as a treatment for diarrhea. Bangladesh Pharmaceutical Journal 25(2): 180-187, 2022 (July)